Phytochemicals of Citrus Fruits: The in-silico Investigation against Sars-CoV-2 Proteins - Jayaprakash, Jayashankar; Renganathan, Rengaswamy Renganathan Arun; Shanthappa, Nanjundaswamy; Karthik, Chimatahalli Shanthakumar; Sandeep, Shadakshari; Santhosh, Arehalli Shivamurthy; Sunderraj, Jayanth Hampapura; Mallu, Puttaswamappa; Nanjundappa, Haraprasad; Vittal, Ravishankar Rai (Trends in Sciences, 2022)
The current pandemic Covid-19 brought about by a newly emerged and highly infectious virus named as Sars-CoV-2 as a worldwide danger, has infected more than 600 million people and number of deaths are continuously rising day by day. Till date there are no medications accessible for treatment. All over the world scientists and researchers are involved in the study of this emerged virus and its lifecycle. Structures of proteins in the life cycle of virus has been revealed in RCSB PDB (Research Collaboratory for Structural Bioinformatics Protein Data Bank) by researchers. Citrus fruits are used to treat many distresses of humans. Literature survey shows that it has various activities. Our research work is meant to identify the phytoconstituents which are having phenolic composition and good antiviral and antioxidant properties from citrus fruits against Covid-19 proteins (spike binding domain with ACE2 receptor and spike binding domain with Main protease) and to know its in-silico molecular basis. In this study, about 25 compounds from citrus fruits which is having a good antiviral and antioxidant properties and also phenolic composition were employed for molecular docking analysis, molecular dynamic simulation studies and ADME studies. Based on present study 2 compounds from Citrus fruits acted well against the Covid-19 proteins. The MD simulations were employed to identify Hesperidin and Procyanidin B2 as hit compounds. Further ADME analysis were studied for top 2 compounds, these compounds can be further taken for in-vitro studies to know the effective activity against Covid-19. HIGHLIGHTS Citrus fruit phytochemicals are fascinating core, which shows an excellent anti-viral, anti-inflammatory and antioxidant properties The SARS-CoV-2 is newly emerged and highly infectious virus, has infected more than 600 million people and number of deaths are continuously rising day by day Molecular docking analysis, Molecular dynamics simulation ADME studies was carried out Compound Hesperidin and Procyanidin B2 showed a good inhibitory activity against SARS-CoV-2 proteins GRAPHICAL ABSTRACT